Effect of Ramadan Fasting on Oxidative Stress and Thyroid Functions. - Yeşim GÖÇMEN, Ayşe; ÇAĞLAYAN, Kasım; SILIT, Emir (Journal of Digestive Disorders And Diagnosis, 2019)
Ramadan fasting might be beneficial for digestive health, if appetite control and balanced diet is achieved. In this study we aimed to evaluate the effect of Ramadan fasting on thyroid glands and some biochemical parameters in Turkish people living in Yozgat region. A total of 40 healthy subjects (20 men and 20 women) aged between 21-50 years were randomly recruited. Thyroid nodule volumes, thyroid hormones, body weights, glucose, total Cholesterol (TC), and oxidant stress index (OSI) were measured before Ramadan and at the end of Ramadan. There were beneficial changes in blood parameters and thyroid volumes, after one month of fasting during Ramadan compared with baseline. The Ramadan fasting might affect the radiological and biochemical parameters in healthy Turkish subjects. To improve the favorable digestive health in Ramadan fasting, diet and lifestyle modifications such as, increased intake of healthy foods and physical exercises might be recommended.
Keywords: Ramadan; fasting; thyroid; hormones; oxidative stress